Clinical Presentation, Echocardiographic Findings, Treatment Options Available for Ventricular Septal Defect in Children: A Study in a Tertiary Care Military Hospital - Sarker, Md Ferdousur Rahman; Moniruzzaman, Mohammad; Bhuiyan, Mohammad Nazmul Islam; Khan, Md Ashfaque Ahemmed (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Ventricular Septal Defect (VSD) is the most common congenital heart defects. Early diagnosis, appropriate treatment and transcatheter VSD closure with newer devices in favorable cases, decrease the need for surgical interventions and mortality. Objectives: To determine the clinical presentation, echocardiographic findings and the treatment options available for VSD in Paediatric Cardiology Department, Combined Military Hospital (CMH) Dhaka. Methods: It was a cross sectional observational study carried out in the department of Paediatric Cardiology, CMH Dhaka. Forty six isolated ventricular septal defect cases were diagnosed by echocardiography. Clinical features, echocardiographic findings and treatment options of all 46 cases were observed and recorded in pre formed data sheet and statistical analysis was done in statistical software SPSS version 25. Results: Among the 46 patients of VSD, majority 20(43.48%) were in age group 0-6 months. Most of them were male 24(52%). Common presenting features were dyspnea on exertion 23(50%), cough 30(65.20%), head sweating 23(50%), and feeding problem in 34(73.91%). VSD in 27(58.6%) patients were <5mm, 15(32.6%) were 5-10mm and 4(8.7%) had size >10mm. Most of the VSDs were perimembranous 31(67.39%). Among the 46 cases medical management was given to 20(43.5%), device closure was done in 10(21.7%) patients and surgical interventions done in 16(34.8 %) patients. Conclusion: Most of the VSD patients presented at an earlier age some of them were undergone device closure and some require surgical interventions that were not suitable for device closure. Patients those presented lately developed pulmonary hypertension. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 22-26